DASAR-DASAR PENGEMBANGAN KURIKULUM - Eka Puspita Sari; Nurhafiza, Rati Rania, Sylvi Carolia (ADISAM PUBLISHER, 2026)
Curriculum development is a process that plans, produces a better tool based on the results of an assessment of the existing curriculum, so as to provide better teaching and learning cinditions. In other words, curriculum development is an activity to produce a new curriculum through the steps of curriculum preparation based on the results of assessments carried out during a certain period.